Utilization of interplay between inflammation and cancer in the development of compounds with anticancer activity - Dobričić, Vladimir; Keta, Otilija (Archives of Pharmacy, 2022)
It is estimated that up to 20% of cancer-related deaths are linked with inflammation. Inhibition of inflammatory enzymes COX-2 and 5-LOX impacts cancer cells directly, or indirectly via tumor microenvironment. Wider anticancer potential has been investigated for a small group of COX-2 inhibitors, while there are no such data for dual COX-2 and 5-LOX inhibitors. The main aim of the project is to select the most promising anticancer drug candidates from a group of COX-2 and dual COX-2 and 5-LOX inhibitors (newly synthesized and previously synthesized). New compounds will be designed using structure-based and ligand-based in silico methods and synthesized. Cytotoxicity will be evaluated towards four cancer cell lines by MTT assay. Wider anticancer potential of selected compounds, which includes synergism with conventional chemotherapy and radiotherapy, inhibition of angiogenesis and activity towards multidrug resistant cancer cells, will be investigated and lead compounds will be identified. Mechanisms of action of lead compounds will be proposed after bioinformatics analysis of genes expression. In vitro evaluation of passive gastrointestinal absorption (PAMPA and BMC), binding to human serum albumin (HPLC and electrochemistry) and metabolism (human liver microsomes) will be performed. QSPR, QSRR and QSMARt models will be created and, together with analysis of metabolism, will be used for the optimization of structures of lead compounds. The project will result in the development of new anticancer drug candidates, make new and strengthen previously established scientific collaborations and give starting point for potential clinical evaluations of lead compounds.